Analysis of Trash Fish Meal Processing Business at PT Samudera Mandiri Sentosa, Halang Muka Island Village, Kubu Babussalam Subdistrict, Rokan Hilir, Riau Province - Nadapdap, Riau Naldu; Arief, Hazmi; Yanti, Chicka Willy (Faculty of Fisheries and Marine, Universitas Riau, 2024)
In the trash fish meal processing business, fish catch constraints are decreasing yearly, so conducting a business feasibility analysis is necessary. This study aims to analyze the total investment, revenue, and profit and explore the feasibility of the trash fish meal processing business in Halang Muka Island Village, Kubu Babussalam Subdistrict, Rokan Hilir Regency. The methods used in this study are case study methods, analyzing secondary data by directly observing objects in the field, and collecting data through direct interviews with trash fish meal processing business owners PT. Samudera Mandiri Sentosa through a descriptive-quantitative approach. The informant in the study was the owner of PT Samudera Mandiri Sentosa as the main informant source. The results of this study are: 1) Total Investment of IDR 897,143,600 with a fixed capital share of IDR 892,900,000 and working capital of IDR 4,234,600, 2) Revenue of IDR 1,372,800,000 per year, profit of IDR 522,176,160, 3) Revenue Cost of Ratio (RCR) obtained a value of 1.61, Financial Rate of f Return (FRR) was 58.20% and the Payback Period of Capital (PPC) analysis got a result of 1.72. Based on the feasibility analysis, the trash fish meal processing business at PT Samudera Mandiri Sentosa follows existing criteria/provisions, and it can be concluded that this business is profitable and feasible to run. In the trash fish meal processing business, assistance must be provided with bookkeeping and business management